Prevention of Productive Cows Slaughter through Management of Local State Enterprises - Atien Priyanti; Ismeth Inounu; Nyak Ilham (Indonesian Center for Animal Research and Development, 2017)
Based on the last national livestock census in 2013, the population number of cattle and buffalo have reduced by 15% compared to that in 2011. The highest reduction happened in Java that reached around 24-27%, while that in Bali and Nusa Tenggara was 25%. One of the reasons was caused by decreasing number of cows due to the increase of productive cows slaughtered every year. Number of cows slaughtered in Bali, Nusa Tenggara, and South Sulawesi had reached on average of 72% from total slaughtered, where more than 90% were productive cows. Reasons for slaughtering productive cows were due to: (1) Lower cows price; (2) Limited bulls supply; (3) Local government regulation on inter-island trade; (4) Weak and inconsistent law enforcement; and (5) Lack of understanding on criteria for productive cows by farmers. Increased rate of slaughtered cattle and increasing rate of inter-island trade volumes that higher than the rate of cattle population had caused the decrease of national cattle population. There are currently needs to improve and develop operation slaughter-houses under management of local state enterprise. The management applies on certain mechanisms that sort of incoming productive females according to different grades into allowable to be slaughtered and selected for breeding females, which could be further traded inter-island as supplier of cows for other regions. This strategy may help the central government to meet the demand for productive cows, particularly in Sumatera and Kalimantan which have abundance of feed biomass resources. Policy support is needed as instruments for all interested stakeholders including those who are willing to invest in cattle development such as oil-palm estates.